2023
DOI: 10.1111/andr.13436
|View full text |Cite
|
Sign up to set email alerts
|

Novel sperm chromatin dispersion test with artificial intelligence‐aided halo evaluation: A comparison study with existing modalities

Abstract: BackgroundSperm chromatin dispersion test is a common and inexpensive technique to assess sperm DNA fragmentation, but its subjectivity in assessing a small number of spermatozoa is a disadvantage.ObjectivesTo study the efficacy of a new sperm chromatin dispersion test kit (R10) combined with an artificial intelligence‐aided halo‐evaluation platform (X12) and compare the results to those of existing sperm DNA fragmentation testing methods.Materials and methodsSemen samples from normozoospermic donors (n = 10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Recently, models for automation of the SCD test have been introduced, 39–41 but most of them are semi-quantitative classifier models. We establish our modified standard upon the commonly used definition of the relative halo radius and take into consideration the variable staining status and inter-operator variability.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, models for automation of the SCD test have been introduced, 39–41 but most of them are semi-quantitative classifier models. We establish our modified standard upon the commonly used definition of the relative halo radius and take into consideration the variable staining status and inter-operator variability.…”
Section: Resultsmentioning
confidence: 99%
“…However, we still have some way to travel. The development of novel consensus methods for detecting DNA damage, 14 determining which patients should be assessed, 30 elucidation of the relative importance of single and double strand breaks, 31 the significance of oxidative stress in the induction of such damage, 26 the potential therapeutic role for antioxidants, 32 and the consequences of sperm DNA damage in terms of male fertility and the health and wellbeing of the offspring, 23,24,26 all need to be elucidated before the true clinical significance of such damage becomes clear.…”
Section: Discussionmentioning
confidence: 99%
“…9 Diagnostic methods such as the MiOXSYS ® and OxiSperm ® II have been developed commercially, however neither of these assays appears to provide any meaningful assessment of oxidative stress in spermatozoa, as revealed by Castleton et al and others. [10][11][12][13] Moreover, Kuroda et al 14 observed no significant correlation between sperm DNA damage and oxidative stress as measured by the MiOXSYS ® system, despite the abundance of data revealing the fundamental importance of free radical attack in the induction of sperm DNA fragmentation. 15 Clearly, improved methods are needed to detect oxidative stress in patients presenting with high levels of sperm DNA damage.…”
mentioning
confidence: 99%
“…The sperm chromatin dispersion (SCD) method [7] was employed to determine the sperm DFI. Sperm DNA fragmentation staining kit was procured from Anhui Anke Biotechnology Co., Ltd (Anhui He Food and Drug Supervision and Measures (Quasi) No.…”
Section: Sperm Dna Fragmentation Index Testingmentioning
confidence: 99%